The Mahathir Influence and the Changing Phases of Malaysia-Syria Diplomatic Relations (Journal of International Studies, 2019)
The purpose of this study is to examine Malaysia’s diplomatic relations with Syria through three periods: pre-Mahathir era, the first phase of Mahathir era (1981-2003) and the ‘inter-Mahathir’ years (2003-2018) - referring to the period prior to the return of Mahathir as Prime Minister for the second time in 2018. Ultimately, this study attempts to identify the key factors determining the nature of Malaysia’s bilateral ties with Syria during the Mahathir era. The methodology adopted for this study is qualitative in nature, relying on primary and secondary sources, the former being personal interviews conducted with Tun Dr. Mahathir himself and also with scholars in the field. This paper argues that during the pre-Mahathir era (1958-1981), relations with Syria were very much based on political and diplomatic considerations. However, during the Mahathir era (1981-2003) the emphasis changed due to the significant economic development and Malaysia’s foreign policy took a much more global approach. With this change, economic factors as a foreign policy determinant became more prominent as compared to the pre-Mahathir period. The inter-Mahathir years (2003-2018) did not witness any significant development except for the humanitarian support extended by the Malaysian government during the outbreak of the Syrian conflict in 2011.